If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(c + 4) = 4c + 18 Reorder the terms: 6(4 + c) = 4c + 18 (4 * 6 + c * 6) = 4c + 18 (24 + 6c) = 4c + 18 Reorder the terms: 24 + 6c = 18 + 4c Solving 24 + 6c = 18 + 4c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-4c' to each side of the equation. 24 + 6c + -4c = 18 + 4c + -4c Combine like terms: 6c + -4c = 2c 24 + 2c = 18 + 4c + -4c Combine like terms: 4c + -4c = 0 24 + 2c = 18 + 0 24 + 2c = 18 Add '-24' to each side of the equation. 24 + -24 + 2c = 18 + -24 Combine like terms: 24 + -24 = 0 0 + 2c = 18 + -24 2c = 18 + -24 Combine like terms: 18 + -24 = -6 2c = -6 Divide each side by '2'. c = -3 Simplifying c = -3
| 2x+1=7-10c | | 9-5x=59 | | 2(7-8k)-6(-5k-5)=4-6k+8k-8 | | 5x+18=15x-82 | | -10+x+2x=5 | | 7y-7=4y+8 | | 4(7x+2)=4x | | 152-7x=29x+20 | | -2x+x+6=11 | | 2x-3x-3=-5x-6+x | | 5(k+7)=-5(k+3) | | 4x^2-6x=4 | | -3x+6=11 | | (3x+11)=(5x+6) | | -3x+6=-12 | | 7-8x=100-29x | | 30x-60=120 | | -4x+2y=-6 | | 4(x-1)=4x-15 | | (3x+11)=(5x-6) | | 18x-36x=72 | | 12m^2-13m=35 | | 9x-18=36 | | 10m-44=-10(2-m) | | 2x+25=7x | | -3x+2=3x-8 | | 7z-10-z+4=10 | | 7x-5y=-18 | | (3x-8)*(x+11)=0 | | 4y+20=-y-20 | | 7x+1+x=17 | | 7x+1x=17 |